ANALISIS GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Alfian, Nurul; rohmaniyah, rohmaniyah; Amar, Siti Salama; Kusuma, Andriani; Aina, Muslimatul; Fajar, Achmarul (Universitas Madura, 2023)
This study aims to analyze the effect of good corporate governance on the company's financial performance. This research is a quantitative research. The data source in this research uses secondary data in the form of financial reports. The population in this study is LQ45 companies for the 2020-2021 period and the sampling technique in this study uses this purposive sampling technique so that the sample is 45 companies. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that there is no simultaneous effect of the board of commissioners, board of directors and audit committee on financial performance while partially indicating that among the three variables there is no effect on financial performance.